Simulation of the boron build‐up formation during melting laser thermal annealing. Issue 1 (9th December 2013) - Hackenberg, M.; Huet, K.; Negru, R.; Fisicaro, G.; La Magna, A.; Taleb, N.; Quillec, M.; Pichler, P.; Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; Windl, Wolfgang
Abstract In this work, we present a model describing the boron redistribution during laser thermal annealing in the melting regime based on the adsorption of boron atoms at the solid‐liquid interface. To validate the model, we performed SIMS measurements on silicon samples implanted with boron with an energy of 3 keV and doses of 3 × 1013 cm‐2 and 4 × 1014 cm‐2 annealed with a XeCl excimer laser with a wavelength of 308 nm, a pulse duration of 160 ns, and up to 10 consecutive pulses. After calibration, our model is able to reproduce the measured profiles for the different process conditions. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)